2016
DOI: 10.1186/s40064-016-3281-3
|View full text |Cite
|
Sign up to set email alerts
|

Strata behavior at fully-mechanized coal mining and solid backfilling face

Abstract: Taking Ping Dingshan Coal Mine Group 12 as an example, this paper explains the system layout, key equipment and backfilling technology in detail. It probes into the characteristic of rock strata movement behavior and surface deformation above the gob area through in-site measurement method. The results show that as the overburden strata are effectively supported by the backfill body in mined out areas, there were no evident phenomena as first weighting or periodic weighting during mining process. Besides, infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…As a new partial backfilling method, the research on BCCFM mainly focuses on system layout and mining craft, while there are few studies on strata behavior and ground control of BCCFM. The researches have shown that there are distinct differences in overburden movement and strata behavior between traditional caving mining and gangue backfill mining [18][19][20]. The BCCFM workface integrates backfilling section and caving section within the same workface, and the strata strata behavior of the BCCFM workface will inevitably show its unique law.…”
Section: Introductionmentioning
confidence: 99%
“…As a new partial backfilling method, the research on BCCFM mainly focuses on system layout and mining craft, while there are few studies on strata behavior and ground control of BCCFM. The researches have shown that there are distinct differences in overburden movement and strata behavior between traditional caving mining and gangue backfill mining [18][19][20]. The BCCFM workface integrates backfilling section and caving section within the same workface, and the strata strata behavior of the BCCFM workface will inevitably show its unique law.…”
Section: Introductionmentioning
confidence: 99%
“…This significantly threatens the stability of surface infrastructure [9,10,11]. Many numerical studies have been conducted to predict the stress developed in backfilled gob.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of mining over a certain seam thickness, the overlying rock strata movement and surface subsidence start from the immediate roof, and gradually transfer upward to the ground surface. This significantly threatens the stability of surface infrastructure [ 9 , 10 , 11 ]. Many numerical studies have been conducted to predict the stress developed in backfilled gob.…”
Section: Introductionmentioning
confidence: 99%
“…The development and utilization of coal resources have greatly promoted the development of China [1,2]. However, at present, the coal resources under good mining conditions, such as in shallow buried and large thickness settings, in the eastern part of China have been gradually depleted [3]. To ensure the balance of the mine production capacity, extend the service life of the mine, and improve the recovery rate of resources, some mines must turn into coal resources with relatively difficult mining conditions, such as thin coal seams and coal seams under villages [4].…”
Section: Introductionmentioning
confidence: 99%